EVALUATION OF ORGANIZATIONAL TRANSFORMATION STRATEGY AT PT PERTAMINA PATRA NIAGA (PHENOMENOLOGY STUDY OF GENERATIONAL RESPONSE X, Y, DAN Z) - Panuwun, Petrus Kane Puput; Perdhana, Mirwan Surya (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2022)
The current development makes many organizations have to transform. The organizational transformation involves shifting the direction of the organization from its current position to the more desired position, as an effort to respond new and better challenges and opportunities. This research is an evaluation of the organizational transformation strategy which recently happens at PT Pertamina Patra Niaga (PPN), by examining the perception of every generation (X, Y, and Z) towards the organizational transformation process. This is very important in order to develop an ideal change management strategy model according to the intergenerational perceptions, thereby increasing the success of the organizational transformation that has been set, and ultimately increase the organizational performance. This qualitative research uses a phenomenological approach which was conducted at PT PPN Regional Central Java (RJBT). Respondents were selected by using purposive sampling method, and then structured interview was conducted to them. All interviews were recorded and transcribed. The research results are presented into two categories, namely: organizational learning (with sub categories include: shared commitment, shared vision, knowledge transfer, and communication patterns) and readiness for change (with sub categories namely: leadership patterns, employee involvement, and employee satisfaction). According to the research outcome and discussion that were conducted, an ideal model of change management strategy is obtained based on intergenerational perceptions. This model consists of 10 strategies which are developed by using a knowledge management approach and the observation of intergenerational behavioral responses. Through those steps, it is expected to increase the success of the organizational transformation that has been set and ultimately increase the organizational performance